The Effect of POE Learning Models (Prediction, Observation, and Explanation) with Probing-Prompting Techniques on The Student’s Cognitive Learning Outcomes of SMA Muhammadiyah 3 Jember - Dewi Farida; Joko Waluyo; Kamalia Fikri (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Student learning outcomes are competencies that students have after gaining their learning experience, so indicators of learning success can be seen from student learning outcomes after experiencing the learning process. Student learning outcomes can be improved through the use of learning models, one of which is by applying the POE learning model (Prediction, Observation and Explanation) with probing-prompting techniques. The purpose of this study was to determine the effect of POE learning models (Prediction, Observation and Explanation) with probing-prompting techniques on the cognitive learning outcomes of the tenth grade students at SMA Muhammadiyah 3 Jember on the environmental pollution subject. Type of research is a quasy experimental study using a pretest and posttest design. In the experimental class, learning activity was carried out by applying the POE learning model (Prediction, Observation and Explanation) with probing-prompting techniques and the control class, learning activities are carried out by applying conventional learning models. The data of the students' cognitive learning outcomes were obtained through the pretest and posttest scores then analyzed using ANAKOVA test. The application of POE learning model (Prediction, Observation and Explanation) with probing-prompting techniques had a significant effect with a probability as much as 0,000. The affective learning outcomes influenced significantly with a significance value of 0.001 or p<0.05.